Pengaruh Problem Based Learning Berbasis Ethnoscience Terhadap Hasil Belajar Siswa di SMA Muhammadiyah 1 Pontianak: (The Effect of Ethnoscience-Based Problem Based Learning on Student Learning Outcomes at SMA Muhammadiyah 1 Pontianak) - Fiqih, Febriana Nur; Rahayu, Hanum Mukti; Sunandar, Ari (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
One of the problems in learning is low learning outcomes. Problem Based Learning is one of the learning models that can improve learning outcomes. This study aims to determine the effect of Ethnoscience-based Problem Based Learning on student learning outcomes at SMA Muhammadiyah 1 Pontianak. This research was conducted in the odd semester of the 2022/2023 school year. This research used quasi-experimental method with Nonequivalent Control Group Design. Determination of experimental class and control class using random sampling technique. The experimental class amounted to 30 students and the control class amounted to 32 students. The data analysis technique uses cohen's effect size interpretation criteria and statistics using the SPSS Version 22 application. The average pretest score of the experimental class was 30 and the control class was 31. While the average posttest score of the experimental class was 85 and the control class was 73. The results of data analysis using the effect size calculation are 1.08. The value is in the range of ES> 0.8 with high criteria with a category of 93%. The results of this study can be interpreted that there is an effect of Ethnoscience-based Problem Based Learning on student learning outcomes. Abstrak. Salah satu permasalahan dalam pembelajaran adalah rendahnya hasil belajar. Problem Based Learning merupakan salah satu model pembelajaran yang dapat meningkatkan hasil belajar. Penelitian ini bertujuan untuk mengetahui pengaruh Problem Based Learning berbasis Ethnoscience terhadap hasil belajar siswa di SMA Muhammadiyah 1 Pontianak. Penelitian ini dilaksanakan pada semester ganjil tahun ajaran 2022/2023. Penelitian ini menggunakan metode kuasi eksperimen dengan rancangan Nonequivalent Control Group Design. Penentuan kelas eksperimen dan kelas kontrol menggunakan teknik random sampling. Pada kelas eksperimen berjumlah 30 orang siswa dan kelas kontrol berjumlah 32 orang. Teknik analisis data menggunakan kriteria interpretasi effect size cohen dan statistika menggunakan aplikasi SPSS Versi 22. Hasil rata-rata pretest dari kelas eksperimen sebesar 30 dan kelas kontrol sebesar 31. Sedangkan hasil rata-rata nilai posttest dari kelas eksperimen sebesar 85 dan kelas kontrol sebesar 73. Hasil analisis data menggunakan perhitungan effect size yaitu 1,08. Nilai berada di rentang ES > 0,8 dengan kriteria tinggi dengan kategori sebesar 93% hasil dari penelitian ini dapat diartikan yaitu terdapat pengaruh Problem Based Learning berbasis Ethnoscience terhadap hasil belajar siswa.